Different background - Similar strategies: Recruitment in Tanzanian-African and Tanzanian-Asian companies - Henrik Egbert; Gundula Fischer; Sebastian Bredl (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2010)
The literature on enterprises in Sub-Saharan Africa provides evidence that there are significant differences between companies run by members of the majority population and those run by members of minorities. Differences are frequently related to size, age, and certain success indicators. However, it remains unclear whether decisions concerning the acquisition of personnel also diverge. This paper outlines results of a questionnaire survey on recruitment methods of enterprises in Tanzania. The authors tried to discover differences in the recruitment strategies of Tanzanian-African and Tanzanian-Asian companies but found none. The interpretation is that companies operate in similar business environments and face comparable, exogenously given institutional restrictions. Thus, strategies of personnel recruitment seem to be alike.
Keywords: J23; M12; M51; 330; labour market; social capital; organizational culture; recruitment methods